Analisis Kesulitan Siswa Dalam Menyelesaikan Soal Pokok Bahasan Persamaan Garis Singgung Lingkaran Ditinjau Dari Level Berpikir Van Hiele Pada Siswa Kelas Xi Sma Muhammadiyah 1 Karanganyar - Utami, Novia Dwi; , Dra. Sri Sutarni, M.Pd (2017)
The purpose of this study is to describe the location of the difficulties experienced by students and the cause of students' difficulties in completing questions of the geometry of circles tangent equation in terms from Van Hiele levels of thinking. The type of this research is descriptive qualitative. The subjects were students of class XII IPA 1 SMA Muhammadiyah 1 Karanganyar Year 2016/2017. Data collection methods used were a test, interview, documentation and observation. Data analysis techniques through Data Reduction, Data Display, and Conclusion. Van Hiele levels of thinking consists of five levels, but in this study only uses three levels, which is visualization (level 0), analysis (level 1), the deduction informal (level2). The results of this study stated that the location of the difficulties experienced by the students is at the level of visualization. They are difficult to distinguish the equation of a tangent to the circle passing through a point or known to the slope and the level of informal deduction. The student also experiences difficulties to enter the data into the formula and still have difficulties in performing arithmetic operations. Factors that causing students difficulties generally are poor understanding the concept of equation tangent to the circle and not practicing counting integer operations.